Estimating low-enthalpy geothermal energy potential for district heating in Santiago basin–Chile (33.5 °S). (April 2015) - Muñoz, Mauricio; Garat, Pablo; Flores-Aqueveque, Valentina; Vargas, Gabriel; Rebolledo, Sofía; Sepúlveda, Sergio; Daniele, Linda; Morata, Diego; Parada, Miguel Ángel
Abstract: This work presents the results of a regional-scale estimation of low-enthalpy geothermal resources for district heating in the Santiago basin. The purpose of this work is to identify promising areas for the development of this type of renewable energy. The estimation was based on comparison of soil thermal properties and hydrogeological parameters, using Geographic Information System (GIS). To determine the geothermal potential, Ground Source Heat Exchanger (GSHE) coupled with heat pump was used to supply a fixed demand equivalent to the energy required to heat a Chilean standard house. The main barrier for the implementation of a GSHE coupled with heat pump is the well drilling cost, therefore the potential is presented as meters to be drilled in order to install 2 types of GSHE: 1) Borehole Heat Exchanger (BHE) and 2) Groundwater Heat Exchanger (GWHE). To assess the BHE, we used specific Heat Extraction (sHE) of sediments. To evaluate a GWHE, we used depth of groundwater table and groundwater drawdown caused by pumping water to the heat pump. The depth to be drilled ranges from 35 to 105 m in case of the BHE, while in case of the GWHE it ranges from 10 to 400 m. Highlights: We present an estimation of geothermal resources for district heating in Santiago. The estimation was based soil thermal properties and hydrogeological parameters. The main key controlling the favorability for district heating is groundwater table. Groundwater flow improves the efficiency of the heat exchanged with the ground. Hydrological factors help to choose the appropriate ground source heat exchanger.